Improving Subconscious Communicative Competence through Reading Argumentative for Post-Beginner Students in Reading Class, Panca Marga University of Probolinggo - Siti Masluha (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
This study is to analyze the subsconcious communicative competence using argumentative reading for post-beginner student in reading class. The theory used in this study is the communicative competence theory developed by Savignon and linguistic competence developed by Canale and Swain. The method used is classroom action research. The finding of this study is improving the subsconcious communicative competence using argumentative reading. The finding of this study are expected to have not only practical significance, but to a certain degree also theoritical significance.